Firms and Ethnic Wage Differences - David C. Maré; Richard Fabling (Institute of Labor Economics (IZA), 2025)
We examine the contribution to ethnic earnings gaps of differences in the firms where different ethnic groups work. We use linked employer-employee data to estimate worker and firm pay premiums (fixed effects), adapting existing methods to deal with multiple-response ethnicities and weighting. The sorting of workers across firms contributes 10-26 percent of within-ethnicity gender gaps but affects average earnings for men or women within ethnic groups by less than 1 percent, in the face of average ethnic earnings gaps of up to 14 percent. We conclude that within-firm earnings differences are the dominant source of ethnic earnings gaps.
Keywords: J15; J30; J42; J71; 330; earnings; ethnicity; sorting; two-way fixed effects; linked employer employee data